Efektivitas Pelayanan Publik: Studi Pelayanan Call Center 112 Di Kota Samarinda - Dwi Oktaviany Kommala; Inriany Novica Ruminding; Salsabila Salsabila; Serly Fitriana; Anisa Dea Syafira; Cerry Shcneider (Universitas Kristen Indonesia Toraja, 2024)
Public services in Indonesia are really needed by the community, one of which is public services in the form of emergency response services that are ready to serve calls from people who need help quickly. The purpose of this writing is how effective the performance of the State Civil Apparatus is in providing public services through Call Center 112 in Samarinda City and also to find out what efforts are being made by the Samarinda City government to improve the effectiveness of the performance of the state civil apparatus in providing public services through Call Center 112 The method used in this research is a qualitative research approach. The research results show that the effectiveness of the Call Center 112 service management concept at the Samarinda City Communication and Information Service is quite effective because this system has proven its benefits in supporting security and handling emergencies experienced by people in the city of Samarinda. This service allows the public to quickly contact the authorities when an emergency situation occurs, such as a traffic accident, fire, or crime as well as other emergencies.